Tren Penelitian Desain Interaktif dalam Konteks Desain Komunikasi Visual (2015–2024): Analisis Bibliometrik - Bt samsuddin, Yati (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The rapid advancement of digital technology has transformed the paradigm of Visual Communication Design (VCD) from static media into user-centered interactive experiences. This study aims to map trends, influential authors, dominant keywords, and collaboration networks in interactive design research within the VCD context from 2015 to 2024. A bibliometric analysis was conducted using data from Google Scholar with Publish or Perish (PoP), VOSviewer, and Bibliometrix R software. The results reveal a significant increase in publications, with an average growth rate of 25–30% per year, and the emergence of three major research clusters: user experience, visual storytelling, and immersive technology. Dominant keywords such as interaction design and visual communication indicate a shift in research orientation toward experiential and participatory approaches. The study concludes that interactive design plays a strategic role in shaping visual communication that reflects human behavior, cognition, and emotion in the digital era.